RAW 101 : - Canfield, Jon (SYBEX, 2005)
he first introductory book on using Adobe Camera Raw, RAW 101 covers all practical aspects of RAW in Photoshop Elements 3 and Photoshop CS2. Just follow the heavily illustrated, step-by-step examples and you’ll quickly figure out how to attain the greatest accuracy from your RAW files, whether it’s correcting shadow and highlight detail, fixing white balance, or eliminating noise. Once you see the startling results, you’ll no longer want to rely on your camera to make critical decisions for you.